Description of the clasper of the Southern Thorny Skate Amblyraja doellojuradoi (Pozzi, 1935) (Chondrichthyes: Rajidae) - Delpiani, Gabriela; Figueroa, Daniel E.; Mabragaña, Ezequiel (Zootaxa, 2012)
This work constitutes the first description of the clasper of Amblyraja doellojuradoi. The characterization was based onboth external morphology and the composition of the internal cartilages. A comparison based on these structures with oth-er species of the genus is provided. Considering all of the cartilages, the basal and terminal series of A. doellojuradoi aremore similar in shape and disposition to the equivalent series in A. radiata than to A. hyperborea. However, marked differences in clasper cartilages permit A. doellojuradoi to be distinguished from these congeners.